Characteristics of Childhood Family Violence Experiences in Spanish Batterers. Issue 23 (December 2021) - Teva, Inmaculada; Hidalgo-Ruzzante, Natalia; Pérez-García, Miguel; Bueso-Izquierdo, Natalia
Intimate Partner Violence (IPV) constitutes a major public health problem worldwide. The existing links between childhood family violence experiences and perpetration of IPV during adulthood suggest that violence is transmitted across generations. The aims of this study were to provide new insights into characteristics of the history of childhood family violence in a sample of Spanish convicted male batterers and to examine what typology of batterer (specialist or generalist) is more likely to have had different types of childhood experiences of violence in the family context. Participants were 740 men convicted of IPV whose ages ranged from 18 to 71 years old ( M = 39.74; SD = 10.01). Of them, 305 men were classified as specialist batterers, and 391 men were classified as generalist batterers. Participants completed a questionnaire made ad hoc regarding family of origin violence and sociodemographic aspects. Results showed that, in comparison with generalist batterers, specialist batterers had higher likelihood of having experienced child abuse or maltreatment during their childhood, having experienced physical punishment and child neglect, having their father as the aggressor of such experienced situations of abuse, or maltreatment. Likewise, specialist batterers had higher likelihood of having been witnesses of family violence, having witnessed physical and psychological violence in the family, having witnessed their mother and siblings being the victims and their father being the aggressor when family violence occurred. This study emphasized the need for identifying children exposed to direct and indirect family violence because they could be a vulnerable group for future IPV perpetration. Moreover, variables related to childhood family violence must be considered when developing intervention treatment programs focused on male specialist batterers.